ОСОБЛИВОСТІ КОМПЛЕКСУВАННЯ СЕКЦІЙ ОБВИТКИ ТРАНСФОРМУЮЧОГО ЕЛЕМЕНТА ТРАНСФОРМАТОРНО-КЛЮЧОВОЇ ВИКОНАВЧОЇ СТРУКТУРИ ПЕРЕТВОРЮВАЧА ЗМІННОЇ НАПРУГИ - Липківський, К.О.; Можаровський, А.Г. (Інститут електродинаміки Національної академії наук України, 2018)
The transformer-and-switches executive structure implements the transformation of an AC voltage by changing the voltage transmission coefficients by changing the number of turns of the transformation element. The main criterion of the quality of the transformer-and-switches executive structure is the efficiency of the use of transforming and switch elements. It is shown the expediency of taking into account other criteria of the quality of the device, including the number of simultaneously operating switch elements. This number determines the total energy losses in these elements and the necessary parameters of heatsink for the heat rejection from semiconductor switch elements. References 12, figures 3.